Kantenfilter: Medizinische Indikation und klinischer Einsatz = Edge filters : medical indications and clinical application - Rohrschneider, Klaus; Bach, Michael (Der Ophthalmologe, 2018)
Edge filters are used in aphakic eyes as a substitute of the natural cut-off filter of the intact eye or in other causes of a lack of light absorption in the eye itself. Furthermore, they can remedy light adaptation disturbances, especially in hereditary retinal diseases and retinal dystrophy. They enhance contrast and reduce glare. In order to choose an adequate cut-off filter it is necessary to let the participants test various filters before prescription. Because of the (absolute) absorption of blue light, cut-off filters normally lead to a loss of ability to drive.
Gesehen am 10.04.2019